P159 MECHANISM OF DIET-DERIVED METABOLITES: A BEDSIDE TO BENCH INTERVENTION IN ULCERATIVE COLITIS. (7th February 2019) - Muthu, Mukil Marutha; Matthew, Phillips; Quintero, Maria; Pignac-Kobinger, Judith; Garces, Luis; Fernandez, Irina; Santander, Ana M; Chen, Chi; Abreu, Maria
Abstract: : Ulcerative colitis (UC) is a chronic inflammatory bowel disease. Growing evidence demonstrates that the diet, gut microbiota and metabolites have a significant impact on UC. A high fat diet with less fiber have been linked to an increased risk of UC development. However, these complex interactions on UC are not well understood. We are performing a diet intervention study in which UC patients in remission or mildly active are sequentially given a high fat or low fat diet (4 weeks of each, 2 week wash out in between). The cross-over design and catering minimize variation. In a limited sample size of 8 patients, quality of life (QoL) was significantly improved based on low fat diet. We tested the hypothesis that this diet intervention led to a change in the microbiome (16s rRNA sequencing) and the fecal metabolites. Methods: 16S rRNA sequencing (Illumina MiSeq platform) was performed at Second Genome and used QIIME2 for microbiome analysis. The metabolites were analyzed (targeted and untargeted) by high resolution ultra-performance liquid chromatography (UPLC) and quadrupole time-of-flight (QTOF) mass spectrometry system in Dr. Chen's lab. Stool samples were collected at 4 time points. Results: 16S rRNA microbial profiling did not reveal any significant differences in this small sample size. We did find significant differences, however, in fecal metabolites. The untargeted analysis showed strong separation between the LFD and HFD groups. A few groups of fecal metabolites, including fatty acids (C12-C18), N-acylamino acids (N-oleoyl phenylalanine, N-palmitoyltaurine) and dehydrolithocholic acid were positively correlated with a HFD, while multiple amino acids (glycine, alanine), and AA metabolites (phenyllactic acid) were positively correlated with a LFD. Among these diet-responsive metabolites, lauric acid was increased by HFD even though no exogenous dietary intake of lauric acid (i.e. coconut or palm oil) was in either of the diets. This pilot study highlights new strategies to formulate precision medicine approaches for increasing the efficacy of dietary interventions in UC treatment.